Providing An ECRM Framework For Malaysian Retailing Industry Based On Consumer's Perspective - Teo, Kok Boon (2007)
This research paper focuses on the understanding and development of ECRM model for Malaysian retailers to help them implement successful ECRM strategy on Internet and at the same time to add value to their retailing business.